A Aprendizagem Baseada em Problemas (ABP) na formação inicial do professor de música - Barros, Matheus Henrique da Fonsêca (2020)
The purpose of this study was to analyze the experience of implementing Problem-Based Learning (PBL) in music teacher education. Using a qualitative approach, an action-research took place in the Instituto Federal de Educação, Ciência e Tecnologia (IF) in the Northeast of Brazil with Music Education Degree students and selected staff. Participant students were enrolled in an elective class (“APM 058 - Special topics in music education”) between September 2019 and February 2020. The methodology consisted of four stages: initial stage; recognition stage; diagnostic stage and pedagogical intervention stage. During the diagnostic stage, participants answered a questionnaire used to gage areas of difficulty in their experience as music teachers in primary and secondary school levels. The pedagogical intervention was carried out by in-class activities based on five problematic situations in light of the diagnostic stage findings. Moreover, additional data was gathered through roundtable interviews with students, participant observations with audio recording, field and class diaries, and semi structured interviews with three administrative faculties. The theoretical references of the study cover two main aspects: the first is related to the music teacher education based on a reflective perspective as well as the concepts of habitus and field, proposed by Pierre Bourdieu, and their developments in the field of musical education; the second, concerns PBL, its historical overview, theoretical basis and the need for its operationalization and practice. In conclusion, the data’s interpretative analysis indicates that PBL can enrich the process of music teacher’s education by bringing the formative stage closer to the practical world, through problems that present real-life situations in teaching primary and secondary school levels. The effectiveness of its implementation depends on institutional, curricular, and cultural factors as well as the knowledge of the frameworks of PBL. PBL’s dynamics reconfigures the teacher/student relationship, promotes the development of learning autonomy and the recognition of musical teaching identity. It also fosters group-work skills that stimulate cooperation and mutual analysis, in addition to encouraging reflective professional practice. The action-research carried out provided theoretical and practical pillars capable of supporting indications of pedagogical action with PBL for music teacher education.